(untitled) (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
The article is based on a study of the structural funds used in Romania during 2007-2014. The analysis examines all the programs carried out in the mentioned period in Romania. The study focuses on several indicators personally elaborated, which are meant to reveal the major differences between the operational programs and in each operational program by itself by comparing the ratios resulted. This research can be considered as an objective summarized examination of the first stage of EU funding in Romania.